Pemanfaatan Limbah Serat Tebu Pada Campuran Stone Matrix Asphalt Yang Menggunakan Batu Sungai - Antonius Tandirau Sombo; Alpius; Sufiati Bestari (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study was intended to determine the characteristics of Stone Matrix Asphalt (SMA) using Tandung river stone, North Toraja Regency with added sugarcane fiber waste with levels of 0%, 1%, 2%, 3% and 4%. The methodology of this research is to test the characteristics of coarse, fine, and filler aggregates and then design the composition of the Stone Matrix Asphalt (SMA) mixture with the addition of sugarcane fiber waste and also conventional Marshall testing to determine the characteristics of the mixture and the Marshall Immersion testing to obtain residual Marshall stability values. The results of the Marshall immersion test for the Stone Matrix Asphalt mixture with the optimum sugarcane fiber waste content of 4,00% obtained the remaining marshall stability/ durability of 95,45% meeting the general specifications of Bina Marga 2018.